Quantifying upper ocean turbulence driven by surface waves - D'Asaro, EA; Thomson, J; Shcherbina, AY; Harcourt, RR; Cronin, M; Mark Hemer; Fox-Kemper, B (2014)
Nearly all operational ocean models use air-sea ﬂuxes and the ocean shear and stratiﬁcation to estimate upper ocean boundary layer mixing rates. This approach implicitly parameterizes surface wave effects in terms of these inputs. Here we test this assumption using parallel experiments in a lake with small waves and in the open ocean with much bigger waves. Under the same wind stress and adjusting for buoyancy ﬂux, we ﬁnd the mixed layer average turbulent vertical kinetic energy in the open ocean typically twice that in the lake. The increase is consistent with models of Langmuir turbulence, in which the wave Stokes drift, and not wave breaking, is the dominant mechanism by which waves energize turbulence in the mixed layer.Applying these same theories globally, we ﬁnd enhanced mixing and deeper mixed layers resulting from the inclusion of Langmuir turbulence in the boundary layer parameterization, especially in the Southern Ocean.